2008
DOI: 10.1007/s12028-008-9153-0
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Cerebral Vasoconstriction by Dantrolene and Nimodipine

Abstract: Introduction-Cerebral vasoconstriction is associated with increased cytosolic Ca 2+ concentration in vascular smooth muscle, presumably due to Ca 2+ influx and Ca 2+ release from intracellular stores. We tested the hypothesis that dantrolene (a blocker of Ca 2+ -induced Ca 2+ release from the ryanodine receptor channel on the sarco-endoplasmic reticulum) would potentiate the action of nimodipine (a voltage-dependent L-type Ca 2+ channel blocker, considered standard therapy for SAH) in inhibiting the vasoconstr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
36
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 59 publications
4
36
0
Order By: Relevance
“…8A) is consistent with findings in other rat arterial smooth muscle preparations, including aorta, superior and inferior mesenteric (59), coronary (70), and main pulmonary arteries (80), but not basilar arteries (65). Our real-time PCR data, however, show that RyR2 is the most abundant transcript in rat cerebral artery myocytes, with RyR3 less highly expressed and RyR1 barely detected (Fig.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…8A) is consistent with findings in other rat arterial smooth muscle preparations, including aorta, superior and inferior mesenteric (59), coronary (70), and main pulmonary arteries (80), but not basilar arteries (65). Our real-time PCR data, however, show that RyR2 is the most abundant transcript in rat cerebral artery myocytes, with RyR3 less highly expressed and RyR1 barely detected (Fig.…”
Section: Discussionsupporting
confidence: 91%
“…8B). Using PCR, it has recently been reported that only RyR3 RNA can be detected in rat basilar arteries (65). In both this study and ours, animals of same species, strain, and age were used.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…On the other hand, there are clinical indications that the specific RyR1 antagonist Dantrolene Ò may attenuate cerebral vasoconstriction [24,25]. So far, RYRs had been implicated in several diseases of skeletal muscle (RYR1) and heart muscle (RYR2) [26].…”
Section: Discussionmentioning
confidence: 99%
“…Dantrolene, an already US Food and Drug Administration (FDA) approved ryanodine-receptor (RyR) blocker, is a promising pharmacological agent for improving outcomes after aSAH given its dual mechanism; it is neuroprotective,2 3 and in animal models inhibits cerebral vasoconstriction alone and exponentially more in combination with nimodipine 4. In fact, the common pathway for cVSP and neurotoxicity is the continuous elevation of intracellular Ca 2+ , resulting from the influx of extracellular Ca 2+ and, to a much higher degree, release from the largest intracellular Ca 2+ -store, the endo/sarcoplasmatic reticulum, mediated by the RyR 5 6.…”
Section: Introductionmentioning
confidence: 99%